The evaluation of steam condensing process in the presence of fouling on the example of a single tube derived from the steam power plant heat exchanger - Tomasz Hajduk (Scientific Journal of Gdynia Maritime University, 2023)
Additional thermal resistance caused by fouling gathered on the heat transfer surfaces of condensers and regenerative heat exchangers within steam power plants most often results in heat transfer process deterioration. It manifests itself, among others, in a reduction in the heat power of a given heat exchanger and in an increase in the working pressure on the steam side. Moreover, the gathered deposits sometimes create irregularities with a diverse geometric structure, hence the description of the steam condensation process is not always clear in interpretation due to the coexistence of many phenomena at the same time. The paper presents selected theoretical issues regarding the presence of sediments on heat transfer surfaces as well as it shows the results of own experimental research on heat transfer within the steam condensation on a single pipe covered with sediments derived from the heat exchange apparatus of a steam power plant.